EVALUATION OF OUTCOMES OF PRIMARY PSEUDOPHAKIC RETINAL DETACHMENT SURGERY - (:unkn) unknown (ISTANBUL UNIV, FAC MEDICINE, PUBL OFF, 2021)
Objective: To evaluate the results of pars plana vitrectomy (PPV) alone and combined with circumferential scleral buckling (CSB) surgeries for aphakic or pseudophakic rhegmatogenous retinal detachment (RRD). Materials and Methods: Thirty-seven eyes of 37 patients who underwent PPV (20 and 23 Gauge) alone or PPV combined with CSB due to pseudophakic or aphakic primary RRD were included in the study. Postoperative anatomical success (AS) and functional success (FS) were evaluated. The AS was defined as a completely flattened retina without any subretinal fluids after the removal of the silicone oil tamponade, if used. The FS was defined as two or more decimal improvements in the logMAR equivalent of Snellen visual acuity. Results: The mean age of the patients was 62.43 +/- 11.40 (32-80) years, 21 (56.8%) patients were male, and 16 (43.2%) were female. The mean follow-up time was 21.35 +/- 16.86 (6-84) months. PPV combined with CSB were performed in 23 patients. AS was found to be 86.5% (32/37), FS was 49.9% (17/37). No statistically significant difference was observed in both AS and FS between the groups according to preoperative PVR presence (AS-p=0.61, FS-p=0.14), preoperative macular involvement (AS-p=0.98, FS-p=0.36), whether PPV combined with CSB (AS-p=0.97, FS p=0.29), and the type of tamponade (p>0.05 in all). Conclusion: PPV with or without CSB is safe and effective in cases with primary pseudophakic retinal detachment and achieves good AS without being affected by the presence of PVR or macular involvement. However, functional success may not always follow.
Keywords: Pseudophakic retinal detachment; pars plana vitrectomy; circumferential scleral buckling; PARS-PLANA VITRECTOMY; EXTRACAPSULAR CATARACT-EXTRACTION; SCLERAL BUCKLE